2016
DOI: 10.1186/s12936-016-1436-x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vector research and control in Haiti: a systematic review

Abstract: BackgroundHaiti has a set a target of eliminating malaria by 2020. However, information on malaria vector research in Haiti is not well known. This paper presents results from a systematic review of the literature on malaria vector research, bionomics and control in Haiti.MethodsA systematic search of literature published in French, Spanish and English languages was conducted in 2015 using Pubmed (MEDLINE), Google Scholar, EMBASE, JSTOR WHOLIS and Web of Science databases as well other grey literature sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…The study suggested that the mass LLINs had no significant effect in preventing clinical malaria (odds ratio = 0.95, 95% confidence interval = 0.68, 1.32). 37 Although the study design could not rule out a modest impact that was not measurable, these findings are compatible with vector behavior studies in Haiti from the published literature, 32 as well as from recent evaluations conducted by the PNCM and CDC, that show predominantly outdoor biting but some indoor biting during early evening hours (Impoinvil D, personal communication). After this experience, the PNCM targeted LLIN distribution to the medium- and high-transmission strata of the country.…”
Section: Ensuring Efficacy Of Antimalarial Drugs and Preventive Intersupporting
confidence: 76%
See 1 more Smart Citation
“…The study suggested that the mass LLINs had no significant effect in preventing clinical malaria (odds ratio = 0.95, 95% confidence interval = 0.68, 1.32). 37 Although the study design could not rule out a modest impact that was not measurable, these findings are compatible with vector behavior studies in Haiti from the published literature, 32 as well as from recent evaluations conducted by the PNCM and CDC, that show predominantly outdoor biting but some indoor biting during early evening hours (Impoinvil D, personal communication). After this experience, the PNCM targeted LLIN distribution to the medium- and high-transmission strata of the country.…”
Section: Ensuring Efficacy Of Antimalarial Drugs and Preventive Intersupporting
confidence: 76%
“…Unlike the primary vectors in sub-Saharan Africa where LLINs have been well-documented to significantly decrease malaria transmission, disease burden, and child mortality, 26 28 the malaria vector in Haiti is Anopheles albimanus which tends to bite outdoors and at variable times throughout the evening and nighttime hours—situations that are not typically protected by bednet use. 29 – 32 The results from studies assessing the impact of LLINs in countries in the region of the Americas that have the same vector are mixed. 33 36 …”
Section: Ensuring Efficacy Of Antimalarial Drugs and Preventive Intermentioning
confidence: 99%
“…The primary vector is presumably Anopheles albimanus , which is the only confirmed vector and the only species reported in the country over the last decade [ 10 ]. Despite P. falciparum endemicity in Haiti, there is no evidence of in vivo clinical resistance of the parasite to chloroquine, which is still used as a first-line treatment for uncomplicated malaria [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have found no resistance of An. albimanus to pyrethroids; resistance to dieldrin and fenitrothion is thought to be low, and only resistance to DDT is considered to be widespread [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This effort is part of an overarching goal by these countries to create a malaria-free zone across the Caribbean by 2025 [1]. The main malaria-causative parasite in this region is chloroquine-susceptible Plasmodium falciparum transmitted mainly in Haiti by Anopheles albimanus mosquitoes [2]. Overall, malaria transmission in Haiti is low, with approximately 21,000 con rmed cases in 2016, the year when this study's samples were collected, and a nationwide prevalence of 0.4% [3,4]].…”
Section: Introductionmentioning
confidence: 99%